XRD-Rietveld Method for Evaluating the Leaching Characteristics of Hardened Cement Paste in Flowing Water - Lunchao Zhang; Jikai Zhou; Xu He; Chen Chen (Advances in Civil Engineering)
In order to study the leaching characteristics of hardened cement paste by flowing environmental water, indoor simulated leaching tests of Portland cement paste were carried out at different flow velocities with home-made flow field device and tap water as the erosion medium. By means of mechanical properties tests, X-ray diffraction (XRD), and Rietveld full-spectrum quantitative analysis of specimens after leaching at different ages, the change rules of the flexural strength, main phase composition, and mass fraction of the specimens after leaching were obtained. The results show that, within 90 days, the flow rate in the test has no obvious effect on the leaching of hardened cement paste. With the increase in age, the leaching of hardened cement paste gets more obvious. Rietveld full-spectrum quantitative analysis shows that the leaching of hardened cement paste changes with the relative content of CaCO3 and Ca(OH)2. The higher the relative content of CaCO3 is, the better compaction and leaching resistance the paste has. The leaching resistance of hardened cement paste is also related to the gradient of Ca(OH)2. The smaller the gradient is, the better the leaching resistance is. The Rietveld full-spectrum quantitative analysis method can be used as a method to evaluate the leaching effect of hardened cement paste.